Utilization Of Extract Hyacinth Weed (Eichhornia crassipes [mart.] Solms) on Tomato (Lycopersicon esculentum) - Husnin Yarza (Biological Environment and Pollution, 2022)
This study aims to determine the effect of water hyacinth weed extract on plant height, fresh weight, and dry weight of tomato plants (Lycopersicum esculentum) grown in polybags. The method used was an experimental method with a completely randomized design (CRD) with 5 treatments and 5 repetitions. The treatments in question were P0 (treated without water hyacinth weed extract/control), P1 (treated with 25% water hyacinth extract weed), P2 (treated with 50% water hyacinth extract weed), P3 (treated with 75% water hyacinth extract weed), P4 (treated with water hyacinth extract weed 100%) The best results for the three parameters namely plant height, fresh weight, and dry weight were shown in treatment P4 (100% water hyacinth extract weed treatment) with values ​​of 15.94 cm, 0.756 g, and 0.08 g respectively It can be concluded that the application of water hyacinth extract weed affected plant height, fresh weight, and dry weight of tomato plants planted in polybags.